Risk factors for ovarian cancer by histological phenotype in the Million Women Study - Gaitskell, K (2016)
There is growing evidence that the different histological types of ovarian cancer have diverse origins. Many high-grade serous tumours (the most common type) are hypothesised to arise from the fallopian tubes, while endometrioid and clear cell tumours are hypothesised to develop from endometriosis, and the origins of mucinous tumours are uncertain. If these hypotheses are true, then the population-level risk factors for the ovarian cancer histotypes should likewise vary – but few epidemiological studies have sufficient cases to explore this. This thesis investigates the association between ovarian cancer and various exposures (including tubal ligation and reproductive factors), in a cohort of 1.3 million women, with 8,000 incident ovarian cancers. Participants completed a questionnaire at recruitment, and were followed up for routinely collected information on cancers and deaths using national registries. Cox proportional hazards models were used to estimate adjusted relative risks of ovarian cancer in women by different exposures. Tubal ligation was associated with reduced risks of cancers of the ovary, and also of the peritoneum and fallopian tube; parity and breastfeeding were also associated with reduced risks of ovarian cancer. These associations with ovarian cancer were highly heterogeneous between the different histological tumour types, consistent with hypotheses of their distinct origins. In particular, risks of endometrioid and clear cell tumours were substantially reduced amongst women with tubal ligation, but substantially increased amongst nulliparous women. For high-grade serous carcinomas, there was a smaller but significant reduction in risk with tubal ligation, and no significant association with parity. I also describe some methodological studies I set up for future tissue-based work: developing techniques in image analysis, and a pilot study of obtaining linked pathology reports and tissue samples. The population-level associations demonstrated by histotype are largely consistent with the new hypotheses of the different origins of ovarian cancer histotypes.